Relationship between the Risk of Eating Disorders and the Concentration Capacity of High School Students - Samantha Shania Setijawan; Felicia Kurniawan (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Eating disorder is a change in eating behaviour that affects daily activities, resulting in a vulnerability towards diseases that have several effects on the organ systems, including the neurological system. In teenagers, these disturbances, including a decline in memory, cognitive function, and concentration, will significantly affect daily activities, especially in their studies. The objective of this study was to determine the relationship between the risk of eating disorders and the concentration capacity of high school students aged 12–19 years old. Methods: This study was an observational analytic study conducted cross-sectionally among high school students. Data were collected from September to October 2019. Data were taken using Eating Disorder Examination (EDE) Questionnaire filled out by the respondents, followed by a Stroop test. Data analysis was performed by the chi-square test.Results: Of 294 students, 56.5% had a risk of eating disorder, of whom 66.7% did eating restrain. Of all respondents, 54.8% had poor concentration capacity. There was a relationship between the risk of eating disorder and concentration capacity (p=0.002).Conclusion: The risk of eating disorders has a significant relationship with concentration capacity. An urgent measurement is needed to promote an eating behaviour among adolescents to increase good and productive daily activity.